THE ENGLISH SPEAKING ANXIETY OF FLIGHT ATTENDANT STUDY PROGRAM STUDENTS OF STTKD YOGYAKARTA: IN SEARCH OF CAUSES AND SOLUTIONS - Masyi'ah, Anita Nur (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
Foreign Language Speaking Anxiety (FLSA) has been a challenging issue among English learners. Its impacts for the speakers include preventing them to communicate orally in English. This study scrutinized the specific reasons/causes of the English speaking anxiety of flight attendants study program students in STTKD as well as the solutions to overcome the issue. The participants included four students who joined English for Aviation class and felt anxious when speaking English. Semi-structured interview was employed to collect the data before they were analyzed using thematic analysis technique (Braun & Clarke, 2006). The findings outlined that the students suffered from FLSA because of: (1) the fear of making grammar mistakes and limited vocabulary; (2) the lack of comprehension skill; (3) the lack of preparation and; (4) the fear of negative responses from the audience. Meanwhile, the solutions of such FLSA included (1) learning and reading more of grammar knowledge and improving vocabulary mastery by reading a lot; (2) having more listening and speaking practices; (3) having more preparation, and; (4) focusing on the performance and thinking positively. Therefore, it is implied that students need these coping strategies that can make them less anxious when speaking English. However, pedagogically, it is important to create a less anxious atmosphere during the English speaking learning process to enable them acquire the skill targeted.